La théorie de la « verge de Dieu » dans les tragédies religieuses d’André de Rivaudeau et de Robert Garnier - Di Mauro, Damon (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2005)
In the sixteenth century, writers of both confessions often had recourse to the Old Testament notion of the "rod of God" in order to account for the hand which the wicked had in the evil perpetrated upon their co-religionists. This study proposes to show that the religious tragedies of Rivaudeau and Garnier both drew inspiration from Synesius of Cyrene's doctrine concerning the persecution of the faithful. According to this Greek Father, the divine scourge will not escape punishment by mere virtue of the fact that he has served as the agent of chastisement. This appointed state appears tantamount to reprobation. To be sure, Synesius goes beyond biblical teaching in sullying and demonizing the foe.